Artistic Myth and its Interpretations of Cultural Heritage of the Eastern European Countries in the Popular Animated Films of the Post-Soviet Period - Olena Polishchuk (International Society of Philosophy and Cosmology, 2018)
The article touches upon the issue of the need to study the myth in artistic practices as special phenomenon in the modern social life of Europe countries. The novelty of the study is as follows. We assert that among the newest myths, which significantly affect the value orientations and life standards of modern society, a special place is occupied exactly by the myth of ancient state in newest artistic practices. Such newest myth gives a new interpretation of cultural heritage. We analyses the animation blockbusters all created the newest artistic myth about Rus. We have focus on analyzing the artistic myth as special product of contemporary artistic practices and phenomenon of East-Central Europe culture which was formed as result of post-totalitarian practices and cultural policy of the state. The analysis of its features, as the social and cultural phenomenon, is carried out in our study taking into account problem of post-totalitarian practices in East Europe countries. As result, this myth transposed an idea of "cradle of fraternal nations" in East-Central Europe, and it created the other artistic myth about the Lord of Kiev Vladimir as a naive, capricious and ridiculous ruler of an ancient country